(untitled) (Studia theodisca, 2013)
Alles über Sally (All about Sally) is the fifth novel of the successful Austrian author Arno Geiger. While it was both praised and criticized for being a contemporary adaption of the adultery novel, little importance was attached to the theme of ageing, which pervades the whole novel. Moreover, adulterous female characters over fifty are rare in contemporary German literature. Given these premises, this essay examines the composition of the ageing characters in the novel and provides a discussion of the social construction of images of ageing.